Makna bendera merah putih dalam identitas nasional bangsa Indonesia - Nurbaiti, Talitha Azmi (Maliki Interdisciplinary Journal, 2025)
The Red and White Flag is a national symbol with strong historical, philosophical and ideological values in designing Indonesia's national identity. As an expression of sovereignty and national identity, this flag contains the importance of courage and holiness that have lived from the island kingdom to the era of independence. In the younger generation, especially, in the era of globalization and the dominance of popular culture, the symbolic meaning of the flag has been eroded by the lack of understanding and internalization of national values. This study uses a qualitative approach in the literature research method to analyze the relationship between The Red and White flag symbol and awareness of national identity. The findings of this study indicate that the importance of contextual education, the use of digital media, and the inclusion of families and communities are strategic solutions to strengthen the importance of the flag as part of national identity. Therefore, a complete understanding of the nation's symbol promotes the spirit of nationalism and national integration amidst global challenges.